E-Portfolio for Distance Learning in Elementary School - Suprayekti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Technology is being a part of education development. Every sector use a digital tool to assist their work. The purpose of this study was to determine the effectiveness of distance learning e-portfolios. This research uses mixed methods by combining qualitative and quantitative research methods to be used together in research activity to obtain more comprehensive, valid, reliable, and objective data. The data collected used by collecting and analyzing qualitative data built on quantitative preliminary results to analyze web-based e-portfolios on distance learning in elementary schools. The result of this study state that using e-portfolio assessment wisely to balance classroom assessment and facilitate content knowledge learning is an alternative for teachers. Using a web-based portfolio can minimize the space as a place to store tasks with more diverse formats. Storage can also be neater, making it easy to find and easier to assess by educators.